Fibrewise slightly separation axioms. Issue 7 (3rd October 2021) - Mousa, Mohammed G.; Yousif, Y. Y.
Abstract: The aim of this paper is to look at fibrewise slightly issuances of the more important separation axioms of ordinary topology namely fibrewise said to be fibrewise slightly T 0 spaces, fibrewise slightly T 1 spaces, fibrewise slightly R 0 spaces, fibrewise slightly T 2 spaces, fibrewise slightly functionally T 2 spaces, fibrewise slightly regular spaces, fibrewise slightly completely regular spaces, fibrewise slightly normal spaces. In addition, we announce and confirm many proposals related to these concepts.